Resveratrol Inhibits Pseudorabies Virus Replication by Targeting IE180 Protein - Chen, Xiangxiu; Song, Xu; Li, Lixia; Chen, Yaqin; Jia, Renyong; Zou, Yuanfeng; Wan, Hongping; Zhao, Ling; Tang, Huaqiao; Lv, Cheng; Zhao, Xinghong; Yin, Zhongqiong (Frontiers in Microbiology, 2022)
Resveratrol is a polyphenolic natural product existing in red wine and peanuts and has many pharmacological activities in humans. Our previous studies showed that resveratrol has good antiviral activity against pseudorabies virus (PRV). However, little is known about the antiviral mechanism of resveratrol against PRV. In this study, we found that resveratrol inhibited the nuclear localization of IE180 protein, which is an important step for the activation of early/late genes transcription. Interestingly, the results show that resveratrol inhibited the activity of IE180 protein by dual-luciferase assay. Further, molecular docking analysis shows that resveratrol could bind to the Thr601, Ser603 and Pro606 of IE180 protein. Point mutation assay confirmed that resveratrol lost its inhibition activity against the IE180 protein, which was mutated at Thr601, Ser603 or Pro606. The result demonstrate that resveratrol exerts its antiviral activity against PRV by targeting the Thr601/Ser603/Pro606 site of IE180 protein and thereafter inhibit the transcriptional activation activity of IE180 protein. This study provides a novel insight in the antiviral mechanism of resveratrol against herpesvirus.